Health status of Lebanese university students - Helou, Mariana; Sakr, Rania; Tanios, Alain (International Journal Of Community Medicine And Public Health, 2017)
Background: In order to assess the health status of the students in Lebanese Universities, an epidemiological study was conducted in 3 Lebanese universities during the year 2014-2015. Methods: A standard anonymous questionnaire was distributed in 3 universities in Lebanon; questions were related to socio demographic characteristics, hygiene and lifestyle, social and behavioral life, and diseases. Results: We have collected 500 questionnaires, with a majority of females. Health status was perceived to be good or very good by most of the respondents. This was seen in the group with better sleeping hours. Most of the students were normally to extremely attentive to their hygiene, these students were found to be living at their parents’ house, and have been at least once this year for a medical check-up. Female sex and academic year differences were found related for stress perception and emotional reactions. Conclusions: This study presents some results that are fairly consistent with other foreign surveys. More research is needed to better evaluate the health determents of the students in order to recommend adequate preventive measures and consider generalization of the results to all the students in the Lebanese universities.